2004
DOI: 10.1097/01.ta.0000114069.73054.45
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Embolization Revisited: A Multicenter Review

Abstract: Splenic embolization remains a valuable technique in splenic salvage, especially in higher grade injuries. Complications are common but do not seem to affect outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
233
1
22

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(267 citation statements)
references
References 11 publications
11
233
1
22
Order By: Relevance
“…Distal embolisation is often used for the treatment of focal vascular injuries such as pseudoaneurysms or arteriovenous fistulae [4,23]. Subsequent bleeding may occur because some vascular injuries are initially not detected at angiography or CT due to vasospasm [4,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distal embolisation is often used for the treatment of focal vascular injuries such as pseudoaneurysms or arteriovenous fistulae [4,23]. Subsequent bleeding may occur because some vascular injuries are initially not detected at angiography or CT due to vasospasm [4,23].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent bleeding may occur because some vascular injuries are initially not detected at angiography or CT due to vasospasm [4,23]. However, a recent meta-analysis found that the only difference in short-term outcomes between the two techniques was a higher rate of splenic infarcts after distal embolisation [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The description and prevalence of these complications varies greatly from one series to another (7,(11)(12)(13), resulting from the confusion existing between adverse events related to injury and those related to treatment. The severity of polytrauma is taken into account using the patients' injury severity score (ISS), and several studies have shown that a high ISS was related to more nonsurgical treatment failures (14).…”
mentioning
confidence: 99%
“…They have reported rates ranging between 3 and 14 % [50,51]. A recent review over 1085 patients treated by NOM, 88 of whom submitted to angioembolization (AE), reports a complication rate of 14 % after AE.…”
Section: Nom Of the Spleen And Splenic Abscessesmentioning
confidence: 99%